Transforming Growth Factor -ß1 (TGF-ß1) immunoreactivity in heterotopic grafts of adult dental apical papilla. - Telmo Mezadri; David Tames; Xana Ortolan; José Armengol (Universidad de Concepción., 2015)
To analyze the expression of transforming growth factor-ß1 in heterotopic grafts of adult dental apical papilla. Methodology: The apical papilla of adult Wistar rats was grafted in the ear of the same donor rats 1, 3, 7 and 14 days after grafting, rats were perfused and the tissue containing the graft was processed for histological conventional technique and for immunohistochemical detection of transforming growth factor-ß1. Results: Heterotopically grafted apical papilla developed osteoid dentine. In an early post-grafting stage, odontoblast-like cells organized themselves in palisade and synthesized dentine. However, newly formed dentine possessed the structural appearance of reactive osteoid dentine, which was systematically destroyed by the activity of osteoclaste-like cells. Transforming Growth Factor-ß1 was observed in mesenchymal cells, extracellular matrix of the graft and surrounding host tissue, while odontoblast-like cells were systematically devoid of immunoreactivity. Conclusion: The different expression of transforming growth factor-ß1 between normal tissue and grafted tissue development suggests that in heterotopic graft conditions the inflammatory mediation of the transforming growth factor-ß1 prevails against its morphogenetic role